An improved 2DOF system for predicting the seismic performance of isolated steel moment frames. (December 2022) - Rahgozar, Arash; Estekanchi, Homayoon E.
Highlights: Proposing and designing an improved two-degree-of-freedom (i2DOF) system for isolated steel moment-resisting frames (MRFs). Identifying a dynamic drawback in 2DOF systems for predicting P-Delta and cyclic deterioration effects in 2DOF systems. Utilizing an effective base-level mass (EBLM) in the i2DOF system to overcome the detected dynamic drawback. Predicting the collapse fragility curve of symmetrical and regular low-to-medium-rise isolated MRFs using the i2DOF system. Proposing a simplified bearing design procedure based on the i2DOF system. Abstract: This paper proposes an improved two-degree-of-freedom (i2DOF) system with an incorporated effective base-level mass (EBLM) for evaluating the P-Delta and cyclic deterioration effects of nonlinear isolated superstructures. This study verifies the dynamic response and collapse accuracy of the i2DOF system for actual isolated buildings. The case study buildings are the National Institute of Standards and Technology's (NIST) steel special moment-resisting frames (MRFs) of 4, 8, and 12-stories base-isolated by a friction pendulum bearing (FPB) system. Nonlinear time-history analyses of 22 coupled horizontal–vertical ground motions are performed to verify the i2DOF maximum response when subjected to uplift and pounding effects. The collapse fragility curves of the i2DOF system are compared to those of each corresponding isolated MRF using incremental dynamic analyses (IDA). The results indicate that MRF corner uplifts occur rapidly and do not significantly differ between the i2DOF system and maximum MRF results. The i2DOF system obtains median collapse intensities slightly higher than isolated MRFs, indicating that the i2DOF system somewhat overestimates the accurate collapse results. All types of symmetrical and regular low-to-medium-rise isolated steel MRFs with FPBs are designed using a simplified design procedure based on the proposed i2DOF system with a reasonable seismic response precision.